PERAN AUDIT INTERNAL DALAM PENERAPAN MANAJEMEN RISIKO PERUSAHAAN - Anggie Yolanda Ritonga (Owner : Riset dan Jurnal Akuntansi, 2023)
Industries that experience failure include the result of failure in implementing risk management and could be the end of the industry's operational activities. One way to prevent this failure is by having Enterprise Risk Management (ERM) within the company, this ERM can be used as a methodology used to manage risk strategically from an industry perspective. Departing from these problems, the purpose of this study is to see how the role of internal auditors in assisting the process and implementation of company risk management. This study uses the literature study method obtained from several previous studies with similar topics by adding a discussion from the side that is important for internal auditors to know and carry out corporate culture well because one of the factors for successful implementation of risk management is the creation of corporate governance and corporate culture. the good one. One of the objectives of internal audit is to prevent industrial risks from becoming large. Besides that, good governance is also needed in an industry to reduce these risks. Internal auditors in carrying out their functions by providing advice and recommendations regarding company risk management require cooperation with the company's management unit and good governance so that their role can run properly and produce effective results. If a company wants to implement effective risk management, then the company needs to be open to internal auditors and their staff to jointly create a good organizational culture and the right strategy for implementing sustainable corporate risk management.